PHALLONOPTIC MALATE: A CRITICAL GAZE AT SPACE, VISUAL CULTURE AND PERFORMANCE IN THE STREETS OF OROSA AND BOCOBO, MALATE, MANILA - Yambao, Clod Marlan Krister V. (Humanities Diliman: A Philippine Journal of Humanities, 2010)
Phallonopticism comes from the confluence of the term “phallus” and “panopticon.” I define Phallonotpicism as the configuration of gaze, power and desires specific to but not limited to male performances. By utilizing the term phallonopticism as a heuristic category for analysis, this paper attempts to analyze how Malate’s urban spaces of consumption are gendered. It attempts to map the topography of male homosocial intersubjectivities and the production of desire, power and gaze through male performances, visual culture and structures. Orosa Street is known as the GLTB consumption district of Malate while just a block away, is Bocobo Street, where a “straight” and “heterosexual” male population dwell. The dominance of male homosociality along the said streets has been established through research findings from 2002 - 2009. Through the confluence of political- economic discourse and psychoanalysis this paper will argue that Malate’s urban spaces inform the male subject construction and formation. Furthermore, male homosocialities in both streets activate the production and consumption of gendered spatial politics through complex forms of surveillance, discipline, resistance, and subversion from its stakeholders such as state institutions, the market and Malate’s public.
Keywords: spatial politics, gender, sexuality, performances, masculinity, queer and culture industry